Examining the Effectiveness of a Nursing-Led Telehealth Intervention on Patient Outcomes and Healthcare Utilization among Elderly Patients with Chronic Conditions in HafrAlbatin: A Qualitative Study - Mohammed Obaid Eid Alanazi; Taghreed Obaid Eid Alanazi; Sana Ayad Mufadhi Alanazi; Faisal Abdulaziz Alhamid; Sarah Mohammed Fayez Alharthi; Munairah Talal M Alhamdi; Jawaher Saleh Abdulrahman Binzaid; Nouf Hamdan Abdallah Alamri; Fatimah Rahil Alanazi; Sultan Abdullah R Alshaiqi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: As chronic conditions become increasingly prevalent among the elderly population, innovative approaches like telehealth interventions are being explored to improve patient outcomes and healthcare utilization. This qualitative study aimed to examine the effectiveness of a nursing-led telehealth intervention on patient outcomes and healthcare utilization among elderly patients with chronic conditions in HafrAlbatin, Saudi Arabia, from the perspectives of patients and healthcare providers. Methods: A qualitative descriptive design was employed. Semi-structured interviews were conducted with 15 elderly patients with chronic conditions who participated in a 6-month nursing-led telehealth intervention and 10 healthcare providers involved in the intervention. Thematic analysis was used to analyze the data. Results: Four main themes emerged: (1) enhanced patient empowerment and self-management, (2) improved access to healthcare services, (3) strengthened patient-provider relationships, and (4) challenges and opportunities for telehealth implementation. Patients reported increased confidence in managing their conditions, better adherence to treatment plans, and reduced healthcare utilization. Healthcare providers highlighted the benefits of real-time monitoring, early intervention, and efficient resource allocation. Conclusion: The nursing-led telehealth intervention was perceived as effective in improving patient outcomes and optimizing healthcare utilization among elderly patients with chronic conditions in HafrAlbatin. The findings emphasize the potential of telehealth in enhancing chronic disease management and provide insights for future telehealth implementation in similar settings.